Vaccine diplomacy and the South African Sovereignty Maintenance Struggle within BRICS cooperation - Farai Joseph Chidhume; Taderera Herbert Chisi (Journal of BRICS Studies)
The Covid 19 pandemic has brought an unprecedented litany of challenges diplomatically and in medical technology.  The global pandemic has adversely affected BRICS nations but three of them Russia, China and India have quickly reacted with the invention of vaccines which have been circulated to many countries throughout the world and Africa in particular. Surprisingly while Brazil quickly accepted the readily and easily available Sinopharm vaccine from China which is a fellow BRICS bloc member and South Africa though being the worst affected country in Southern Africa seemed to dither on finding a solution from either China or Russia.  South Africa put more faith initially in AstraZeneca ahead of Sinopharm and Sinovac vaccines from China and Sputnik V from Russia. She has relied enormously on Johnson & Johnson (Netherlands/USA), AstraZeneca and Pfizer. This paper seeks to comment on the silence which has prevailed on the procurement of vaccines from other BRICS allies Russia and China by South Africa. The South African quite diplomatic stance towards vaccines from fellow BRICS bloc members and the time taken to approve the Sinovac vaccine leave analysts with many questions. We ask in this paper, is South Africa protecting its sovereignty or is it circumventing being exploited by the bigger Bloc members?  Research has shown that as part of the arsenal of soft-power diplomacy, big powers including China and Russia have tended to bolster their diplomatic presence in Africa and other developing regions through the vaccineiplomacy. This article will comment on diplomatic, economic and political concerns of South Africa’s scepticism to use the BRICS bloc vaccines in fighting the Covid 19 pandemic despite the devastating effects of the virus in the country.